The Perception of Security Threats in Lithuania: A Human Security Perspective - Janušauskienė, Diana (Qualitative Sociology Review, 2019)
This article presents original research concerning subjective security and the perception of security threats in Lithuania. It is based on an analysis of data collected during qualitative interviews conducted in 2016 within the framework of a project titled Subjective Security in Volatile Geopolitical Context: Traits, Factors, and Individual Strategies. The investigation resides upon individual-based human security theory, and it addresses the threats that individuals consider to be important, as well as the ways in which various perceptions of security form within society.